2019
DOI: 10.1200/jco.2019.37.15_suppl.tps9119
|View full text |Cite
|
Sign up to set email alerts
|

SAVANNAH: A Phase II trial of osimertinib plus savolitinib for patients (pts) with EGFR-mutant, MET-driven (MET+), locally advanced or metastatic non-small cell lung cancer (NSCLC), following disease progression on osimertinib.

Abstract: TPS9119 Background: The toxicity profile of the third-generation EGFR-tyrosine kinase inhibitor (TKI) osimertinib makes it an attractive backbone for combination with other targeted agents, possibly overcoming acquired resistance mechanisms. Combination with a MET-inhibitor is an intuitive approach as MET-amplification was identified as the most common mechanism of resistance to osimertinib in preliminary ctDNA data from the Phase III FLAURA (15% of pts) and AURA3 (19% of pts) studies. Savolitinib (AZD6094, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Currently, even a highly specific targeted therapy, when applied as a monotherapy, is generally not sufficient to eradicate all tumor cells and often leads to tumor recurrence. Based on genomic profiling of resistant and recurrent tumors, combined therapies have been developed for a number of cancer types to reduce the occurrence of resistance and recurrence (44,45). For instance, recent studies have shown that a MET inhibitor combined with a third generation EGFR inhibitor impairs the growth of cancer cells harboring MET amplification (46).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, even a highly specific targeted therapy, when applied as a monotherapy, is generally not sufficient to eradicate all tumor cells and often leads to tumor recurrence. Based on genomic profiling of resistant and recurrent tumors, combined therapies have been developed for a number of cancer types to reduce the occurrence of resistance and recurrence (44,45). For instance, recent studies have shown that a MET inhibitor combined with a third generation EGFR inhibitor impairs the growth of cancer cells harboring MET amplification (46).…”
Section: Discussionmentioning
confidence: 99%
“…Building a mathematical PK/PD modelling framework is a valuable means to integrate extensive datasets of exposure, pharmacodynamic response, and tumour growth to define the target inhibition requirements (and potential variability) for optimal efficacy. Savolitinib is being investigated in combination with osimertinib in NSCLC (SAVANNAH: NCT03778229, TATTON: NCT02143466, and ORCHARD: NCT 03944772), and the modelling approach presented here provides a relevant starting point for the combination setting (Ahn et al, 2019; Choueiri et al, 2017; Oxnard et al, 2019; Sequist et al, 2020; Yu et al, 2019). A PK/PD model relating osimertinib exposure to effects on EGF receptor phosphorylation and TGI has been previously published (Yates et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interim data have shown a response rate of 52% for patients who had previously received first- or second-generation TKIs and 28% for those who had previously received third-generation EGFR-TKIs, with an acceptable safety profile [14]. Based on these data, SAVANNAH, a phase II study that is further investigating osimertinib in combination with savolitinib in patients with EGFR -mutant and MET -amplified NSCLC after progression on osimertinib, is ongoing [15]. NCT02335944 is a phase Ib/II study testing the combination of capmatinib, a highly selective and potent MET inhibitor, and nazartinib, a third-generation EGFR-TKI, while the multidrug phase II platform study ORCHARD is studying different treatment modalities depending on the resistance mechanism involved in the development of resistance to first-line osimertinib, including osimertinib in combination with savolitinib, in patients with MET amplification.…”
Section: Discussionmentioning
confidence: 99%